2015
DOI: 10.1063/1.4933271
|View full text |Cite
|
Sign up to set email alerts
|

Structural, thermal, and photoacoustic study of nanocrystalline Cr3Ge produced by mechanical alloying

Abstract: A thermodynamic analysis of the Cr-Ge system suggested that it was possible to produce a nanostructured Cr3Ge phase by mechanical alloying. The same analysis showed that, due to low activation energies, Cr-poor crystalline and/or amorphous alloy could also be formed. In fact, when the experiment was performed, Cr11Ge19 and amorphous phases were present for small milling times. For milling times larger than 15 h these additional phases decomposed and only the nanostructured Cr3Ge phase remained up to the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…3 Typically SPEX milling is conducted in a mode that maximizes impact energy, as it is widely believed that low impact energy cannot induce alloying. 3 Therefore milling conditions that employ a few large (5 -8 g, 1.3 -1.5 cm diameter [6][7][8][9][10] ) balls are widely used. 3 Very nice results can sometimes be achieved under these conditions 10,11 but the resulting materials can also be microcrystalline as opposed to amorphous or nano-structured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Typically SPEX milling is conducted in a mode that maximizes impact energy, as it is widely believed that low impact energy cannot induce alloying. 3 Therefore milling conditions that employ a few large (5 -8 g, 1.3 -1.5 cm diameter [6][7][8][9][10] ) balls are widely used. 3 Very nice results can sometimes be achieved under these conditions 10,11 but the resulting materials can also be microcrystalline as opposed to amorphous or nano-structured.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore milling conditions that employ a few large (5 -8 g, 1.3 -1.5 cm diameter [6][7][8][9][10] ) balls are widely used. 3 Very nice results can sometimes be achieved under these conditions 10,11 but the resulting materials can also be microcrystalline as opposed to amorphous or nano-structured. 6,8 Recently it has been shown that low energy milling can result in the formation of alloys that are more amorphous than SPEX milled alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Probably the nucleation of GeO 2 occurred during manipulation of blended powders to carry out the XRD measurements at ambient conditions, and is probably restricted to the region close to the particle surface. In a previous article 21 , this oxide phase was also observed, but not discussed, in the XRD pattern of blended powders before milling. For a milling time of 5 h, the intensity of the diffraction peaks of pure Ge was smaller than in the initial mixture and the peaks of GeO 2 are absent.…”
Section: Methodsmentioning
confidence: 77%
“…As shown in Ref. 21, an ideal solution with Cr 11 Ge 19 nominal composition has ΔV/V 0 = 0.415. For 15 h of milling, the interfacial and amorphous volume fractions of the nanostructured Cr 11 Ge 19 alloy occupy an excess volume ΔV/V 0 = 0.248.…”
Section: Xrd and Dsc Resultsmentioning
confidence: 88%
See 1 more Smart Citation